Context-aware Assessment Using QR-codes - Conejo-Muñoz, Ricardo José; Pérez-de-la-Cruz-Molina, José Luis; Barros-Blanco, Beatriz; Gálvez, Jaime; García-Viñas, Juan Ignacio (SAGE, 2013)
In this paper we present the implementation of a general mechanism to deliver tests based on mobile devices and matrix codes. The system is an extension of Siette, and has not been specifically developed for any subject matter. To evaluate the performance of the system and show some of its capabilities, we have developed a test for a second-year college course on Botany at the School of Forestry Engineering. Students were equipped with iPads and took an outdoor test on plant species identification. All students were able to take and complete the test in a reasonable time. Opinions expressed anonymously by the students in a survey about the usability of the system and the usefulness of the test were very favorable. We think that the application presented in this paper can broaden the applicability of automatic assessment techniques.
Keywords: Evaluación educativa - Automatización; Formative assessment; ubiquitous learning; QR codes; Computer-based assessment; Mobile learning